An Analysis of Illocutionary Act in Western Song Lyrics “Espresso By Sabrina Carpenter” - Valentine C.I. Letsoin; Khanna Maulidia ‘Ashr (Musamus Journal of Language and Literature, 2024)
This study aimed to investigate the illocutionary acts in the song lyrics of Sabrina Carpenter's "Espresso." Using a descriptive qualitative method, data were collected and analyzed based on John Searle's (1979) theory of illocutionary acts. The lyrics of "Espresso" contained a total of 22 data of illocutionary acts. The analysis revealed four categories: assertives (11 data), directives (4 data), expressives (4 data), and commissives (3 data). Assertives, the most dominant category, highlighted the speaker's statements and beliefs. Directives and expressives conveyed commands and emotions, while commissives indicated commitments. This study demonstrates how song lyrics function as a medium for emotional and social communication, contributing to understanding language use in art and culture and offering insights for educational approaches integrating popular culture.